Taxonomic revision of the Malagasy Camponotus grandidieri and niveosetosus species groups (Hymenoptera, Formicidae) using qualitative and quantitative morphology - Rakotonirina, Jean Claude; Csősz, Sándor; Fisher, Brian L. (Zootaxa, 2017)
The Camponotus grandidieri species group and Camponotus niveosetosus species group of the Malagasy region are revised. Species delimitation was inferred from the evidence of both qualitative morphological analysis and multivariate morphometry. The multivariate method combined the Nest Centroid (NC)-clustering method and Partitioning Algorithm based on Recursive Thresholding (PART) function to generate hypotheses about species boundaries (clusters) based on 19 continuous morphological traits of minor workers. The proposed species hypotheses were tested by cumulative cross-validated Linear Discriminant Analysis (LOOCV-LDA) and Principal Component Analysis in a shape space (shape PCA). Morphometric ratios for the subsets of minor and major workers were used in species descriptions and redefinitions. Here, eight species are recognized, of which three are newly described and five are redescribed. Four species belong to the Camponotus grandidieri species group: auropubens Forel, efitra n. sp., grandidieri Forel, and maintikibo n. sp.; and four species belong to the Camponotus niveosetosus species group: descarpentriesi Santschi, madagascarensis Forel stat. rev., mita n. sp., and voeltzkowii Forel. Camponotus auropubens aldabrensis Forel and C. olivieri freyeri Santschi are synonymized under C. auropubens. Camponotus grandidieri atrabilis Santschi and C. grandidieri comorensis Santschi are synonymized under C. grandidieri. Illustrated species identification keys for both minor and major castes, taxonomic discussions, images, and distribution maps for each species superimposed on the ecoregions of Madagascar are also provided.